Frequency of azole resistance in clinical and environmental strains of Aspergillus fumigatus in Turkey: a multicentre study - ÇERİKÇİOĞLU, NİLGÜN (My University, 2022)
Objectives Aspergillus fumigatus causes several diseases in humans and azole resistance in A. fumigatus strains is an important issue. The aim of this multicentre epidemiological study was to investigate the prevalence of azole resistance in clinical and environmental A. fumigatus isolates in Turkey. Methods Twenty-one centres participated in this study from 1 May 2018 to 1 October 2019. One participant from each centre was asked to collect environmental and clinical A. fumigatus isolates. Azole resistance was screened for using EUCAST agar screening methodology (EUCAST E.DEF 10.1) and was confirmed by the EUCAST E.DEF 9.3 reference microdilution method. Isolates with a phenotypic resistance pattern were sequenced for the cyp51A gene and microsatellite genotyping was used to determine the genetic relationships between the resistant strains. Results In total, resistance was found in 1.3% of the strains that were isolated from environmental samples and 3.3% of the strains that were isolated from clinical samples. Mutations in the cyp51A gene were detected in 9 (47.4%) of the 19 azole-resistant isolates, all of which were found to be TR34/L98H mutations. Microsatellite genotyping clearly differentiated the strains with the TR34/L98H mutation in the cyp51A gene from the strains with no mutation in this gene. Conclusions The rate of observed azole resistance of A. fumigatus isolates was low in this study, but the fact that more than half of the examined strains had the wild-type cyp51A gene supports the idea that other mechanisms of resistance are gradually increasing.
Keywords: Temel Eczacılık Bilimleri; Sağlık Bilimleri; Eczacılık; Yaşam Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Health Sciences; Pharmacology and Therapeutics; Life Sciences; Natural Sciences; BULAŞICI HASTALIKLAR; İmmünoloji; Yaşam Bilimleri (LIFE); Mikrobiyoloji; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; INFECTIOUS DISEASES; IMMUNOLOGY; Life Sciences (LIFE); MICROBIOLOGY; PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; General Immunology and Microbiology; Pharmacology; Immunology; General Pharmacology, Toxicology and Pharmaceutics; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Pharmacology (medical); Pharmacy; Drug Guides; Infectious Diseases